2016
DOI: 10.1186/s41043-016-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Shigellosis in Nepal: 13 years review of nationwide surveillance

Abstract: Background Shigella is a major cause of gastroenteritis especially in children. In developing countries, the incidence is frequent and results are often life threatening. Changing epidemiology and emerging antibiotic resistance warrants continuous monitoring of susceptibility. The present study highlights the changing epidemiology and drug resistance patterns of Shigella isolated at different hospitals of Nepal over a period of 13 years (Jan. 2003–Dec. 2015).MethodsThis study was carried out in 12 participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
4
16
1
1
Order By: Relevance
“…Both dominated research output in Lassa fever and accounted 64.57% of the total research output. This observation is consistent with previous research in other biomedical research [ 13 , 24 , 30 ]. The United States alone accounted for 40.87% of all research output in this area of study.…”
Section: Discussionsupporting
confidence: 94%
“…Both dominated research output in Lassa fever and accounted 64.57% of the total research output. This observation is consistent with previous research in other biomedical research [ 13 , 24 , 30 ]. The United States alone accounted for 40.87% of all research output in this area of study.…”
Section: Discussionsupporting
confidence: 94%
“…No significant association was found between gender and the other serogroups or between Shigella serogroup and age. Contrary to several other reports, 11,12 we observed no significant seasonality in the distribution of Shigella isolates or in serogroup distribution (i.e., erratic variation between months, but no difference between the wet and dry seasons).…”
Section: Introductioncontrasting
confidence: 99%
“…was higher (7.3%) in gastroenteritis patients of <15 years old than in patients ≥15 years old (4.5%) which is not statistically significant (p=0.432). This finding is consistent with the study done by Khan et al and Shakya et al found Shigella 42.0% and 38.4% and 30.1% respectively [14,18,32]. The reported high prevalence of Shigella spp.…”
Section: Discussionsupporting
confidence: 83%
“…They also reported high prevalence of Shigella spp. from male patient compared to the female [14,32]. Shigellosis or severe bacillary dysentery is a disease of public health importance because it is associated with increased mortality and morbidity especially among the children of developing countries [23].…”
Section: Discussionmentioning
confidence: 99%